The Role of Fate in the Life of Tess in Tess, the D’Urbervilles by Thomas Hardy: The Tragic Fate of Tess: A Victim of Inhumanity (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The principal objective of the present paper is to show the tragic as well horrific role of the fate in life of Tess, a protagonist in Tess, The D’Urbervilles (1992) by Thomas Hardy. Tess is a female protagonist in the novel, who surfers a lots in her life not because of her crime or sin but due to her unfortunate life which is completely under the control of fate. The novel shows that she has to face the wrath of fate or destiny for being a nice human being in the world of inhumanity. In the whole story of the novel, Tess does not commit any crime or sin but she has to face her tragic experience and end of her life in the family as well as outside the family. She is just presented as a victim of fate. It seems that all the disastrous and inhuman incidents of her life are controlled and pre-decided by the fate. Despite being a pure woman, she does not witness and experience a few moment of happiness in her whole life.